PENDAMPINGAN PEMBENTUKAN SATUAN PENGAWAS INTERN (SPI) DI PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) KECAMATAN BANGKALAN - Maduratna, Enggal Sari; Firdaus, Nailufar (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
Community Service S1 Ngudia Husada Madura Health Administration focus on assisting to build an Internal Supervisory Unit (SPI) at the Bangkalan District Community Health Center (Puskesmas). The main purpose of this community service is the design of the SPI organizational structure. The community service method is carried out by workshops and assistance regarding SPI. The paired T test results show that only four components of internal controls are increasing during assistance, namely increasing understanding of the environment of control, control activities, information and communication, and monitoring. The final result of community service is that the design of the SPI organizational structure has been formed and the Bangkalan Puskesmas already knows about the conditions that must be met in forming SPI such as submitting Buputi regulations regarding SPI and Standard Operating Procedure (SOP) SPI.